2005
DOI: 10.1348/147608305x26783
|View full text |Cite
|
Sign up to set email alerts
|

A question of finding harmony: A grounded theory study of clinical psychologists' experience of addressing spiritual beliefs in therapy

Abstract: In spite of the increasing emphasis upon spirituality in the psychological literature, research continues to highlight concerns that issues relating to spirituality are regularly overlooked within a therapeutic setting. The aim of the current study was to develop an account of the way in which clinical psychologists understand and address spirituality within therapy. Semi‐structured interviews were conducted with eight clinical psychologists. The transcripts were analysed using the qualitative methodology of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 31 publications
1
39
0
1
Order By: Relevance
“…Similar considerations were highlighted by participants in Crossley and Salter's (2005) study exploring the experience of addressing spiritual beliefs in therapy as some participants said that they routinely enquired about spiritual beliefs, whereas others said that they waited for the client to initiate discussion. Clearly, more research is needed in this area in terms of the potential benefits or drawbacks of the therapist directly enquiring about AEs at the assessment stage or within the therapeutic session.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Similar considerations were highlighted by participants in Crossley and Salter's (2005) study exploring the experience of addressing spiritual beliefs in therapy as some participants said that they routinely enquired about spiritual beliefs, whereas others said that they waited for the client to initiate discussion. Clearly, more research is needed in this area in terms of the potential benefits or drawbacks of the therapist directly enquiring about AEs at the assessment stage or within the therapeutic session.…”
Section: Discussionmentioning
confidence: 81%
“…given that the topic of spirituality, which could be considered as integral to some AEs, particularly spiritual crisis, mediumship, NDEs, and reincarnation, is rarely discussed in the UK training context (Crossley & Salter, 2005); though research suggests that this may be changing in the US (Brawar, Handal, Fabricatore, Roberts, & Wajda-Johnston, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…O número de estudos que relacionam a espiritualidade com a saúde vem sendo abordado de forma consistente em publicações internacionais e nacionais, chamando a atenção dos profissionais de saúde e pesquisadores. 11,22 Em relação à vitalidade, uma pesquisa com mulheres com câncer de mama, notou que maior espiritualidade esteve diretamente relacionada ao nú-mero total de linfócitos, de células Natural Killer (NK) e de linfócitos T-helper e T-citotóxicos 20 . Quanto às pesquisas com marcadores inflamatórios, há evidên-cias de menores níveis de proteína C-reativa e menores níveis de cortisol nos pacientes que possuem maior frequência religiosa.…”
Section: Discussão Discussão Discussão Discussão Discussãounclassified
“…There is currently growing emphasis on the theme of spirituality in the psychological literature (Crossley and Salter, 2005). A recent study showed that the main domains discussed by Americans in individual psychotherapy included work, family, friends and sexuality.…”
Section: Spirituality and Religion -Conceptsmentioning
confidence: 99%
“…However, the wide range of concepts relating to spirituality was noted as a crucial aspect of the difficulty in working with this field during psychotherapy. The study pointed to the importance of making religion and spirituality concepts more coherent and accessible in order to facilitate professional dialogue in the therapeutic context (Miovic et al, 2006;Crossley and Salter, 2005). In this article, therefore, we have used the definitions suggested by Koenig (2001), who conceptualizes religion as an organized system of beliefs, practices, rituals and symbols designed to help the individual with sacred and/or transcendent aspects, and spirituality as a personal quest for answers in relation to the meaning of life and relationships with sacred and/or transcendent aspects.…”
Section: Spirituality and Religion -Conceptsmentioning
confidence: 99%